Diagnosis of Ion-Exchange Resin Depositions in Paraffin Sections Using Corrective Light and Electron Microscopy-NanoSuit Method - Ooishi, Mako (Diagnostics (Basel), 2021)
Ion-exchange resins are commonly used to treat complications such as hyperkalemia, hyperphosphatemia, and hypercholesterolemia. Gastrointestinal complications may occur as side effects of such treatments. Sodium and calcium polystyrene sulfonate (PS-Ca) are cation-exchange resins comprising an insoluble structure that binds to potassium ions in the digestive tract and exchanges them with sodium and calcium ions, respectively, to promote their elimination. PS crystals are rhomboid, refractive, and basophilic in hematoxylin and eosin staining. To differentiate PS crystals from other ion-exchange resin crystals such as sevelamer and cholestyramine, periodic acid–Schiff, Ziehl–Neelsen, and Congo red staining are usually performed. Here, correlative light and electron microscopy (CLEM)-energy-dispersive X-ray spectroscopy and the NanoSuit method (CENM) was applied to perform a definitive identification of ion-exchange resins. CENM could detect sulfur in PS crystals without destroying the glass slides. Notably, PS retained its ion-exchange ability to bind potassium in paraffin sections. Differential diagnosis of anion-exchange resins, such as sevelamer and cholestyramine, was possible using these characteristics. The phosphorus:carbon ratio was higher in sevelamer than in cholestyramine after soaking paraffin sections in a phosphate solution. Therefore, CENM may be used for the differential pathological diagnosis of ion-exchange resins in paraffin sections.